A prospective observational study to assess peripheral neuropathy in patients receiving weekly paclitaxel chemotherapy - Pansari, Nishtha; Diwan, Arundhati; Rajbhoj, Ashwin (International Journal of Advances in Medicine, 2023)
Background: Peripheral neuropathies are disorders of peripheral nerve cells and fibres. Chemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of anticancer treatment, and it can affect the patient’s long-term survival. The prevalence of CIPN is around 38%. Peripheral neurotoxicity (PN) is a side effect of paclitaxel that can lead to treatment discontinuation. The intensity and severity of neuropathy is more with patients receiving weekly paclitaxel chemotherapy. Methods: 60 patients of CA breast receiving weekly paclitaxel monotherapy who fulfilled inclusion and exclusion criteria were enrolled in the study. Clinical examination and grading of neuropathy was done according to NCI-CTCAE version 4.0. All patient had undergone nerve-conduction studies at baseline and 3 months after baseline. Results: 50% of patients, developed signs symptoms of peripheral neuropathy, out of which tingling sensation was the most common symptom (40%). The incidence of grade 1 peripheral neuropathy at 3 and 6 months were 35%, and 31.66%, while grade 2 neuropathy was noted in 18.33%, and 14.75% of patients, respectively. There was a significant difference in the SNAP value between baseline and 3 months for right ulnar nerve, right and left sural nerve and CMAP for right median nerve, right ulnar nerve, right and left tibial nerves which suggests development of neuropathy during 3 months of paclitaxel chemotherapy. Conclusions: This study provides information on the incidence and severity of peripheral neuropathy in patients receiving weekly paclitaxel chemotherapy, which can help physician in further management.